Seasonal variation and community structure of fishes in the Mahananda River with special reference to conservation issues - Galib, Shams Muhammad; Rashid, Md Abdur; Chaki, Nipa; Mohsin, A B M; Joadder, Md Abdur Razzaq (Journal of Fisheries, 2016)
This study was carried out in the Mahananda River from January to December 2013 with a view to determining the seasonal variation and community structure of fishes along with some conservation issues. Monthly sampling was carried out using traditional fishing gears and fishes were identified based on morphometric and meristic characters. A total of 4082 individuals of native fish species were captured, analyzed and classified into 62 species belonging to 46 genera, 25 families and 9 orders. Cypriniformes and Siluriformes were the dominant fish orders represented by 19 species each and the most abundant family was Cyprinidae (14 species). In addition to indigenous individuals, 9 individuals of 2 exotic fish species (Hypophthalmichthys molitrix and Pangasius hypophthalmus) were also recorded. Among three sampling sites, S-1 was the most diversified in terms of not only the number of individual fish but also the number of species present represented by mean (±SE) individuals of 151.50±25.22 and species of 25.58±3.91. Three distinct fish groups of fish families were revealed from the cluster analysis of similarity. To improve the situation, control of illegal fishing gears, establishment of sanctuaries and legal protection for threatened species are recommended.